Analysis of the Internal Relationship between Economic Management and Enterprise Development - Tian, Lixin; Liu, Xiaohong; Zhang, Xin (Journal of Theory and Practice of Social Science, 2023)
The operation and development of enterprises can reflect the economic development of the whole society to a certain extent. In reality, the business objectives oriented by profit maximization tend to develop into excessive profit-seeking tendencies, which will limit the development of enterprises. In fact, the relationship between economic management and enterprise development is mutual promotion and mutual influence, scientific and effective economic management can often effectively promote the development of enterprises, and enterprises want to develop smoothly, also cannot do without reasonable and scientific economic management.